The Correlation of Physical Fitness Towards an Academic Grades and Physical Education Grades in Senior High School - Ibnu Ahzamil Umam; Moch. Fahmi Abdulaziz (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2026)
The purpose of this study is to determine the relationship between physical fitness and students' academic grades and physical education scores. The type of research conducted was correlational research using a correlation test to determine the relationship between variables, with a sample of 67 students of Senior High School 1 Grabag. The research by taking student physical fitness data using the Nusantara student fitness test (TKPN) and student report card data as a representation of academic scores and physical education scores. The correlation test on the physical fitness variable with academic scores showed a significant result of 0.0001 < 0.05 and had a strong relationship of 0.654 > 0.610. Likewise with the physical fitness correlation test which showed a significant result of 0.0001 < 0.05 and had a strong relationship of 0.621 > 0.610. The results of this study that physical fitness has a positive and strong relationship with academic grades and students' physical education scores. In depth, physical fitness plays a role in increasing brain neuroplasticity through BDNF secretion that optimizes cognitive function, as well as increasing cardiorespiratory capacity that supports movement efficiency and emotion regulation. In conclusion, physical fitness is a crucial internal instrument that directly and indirectly supports students' learning achievement holistically through physical, cognitive, and psychological readiness.